PPy@Fe3O4 Nanoparticles Inhibit Tumor Growth and Metastasis Through Chemodynamic and Photothermal Therapy in Non-small Cell Lung Cancer - Fang, Danruo; Jin, Hansong; Huang, Xiulin; Shi, Yongxin; Liu, Zeyu; Ben, Suqin (Frontiers in Chemistry, 2021)
Non-small cell lung cancer (NSCLC) is considered to be a principal cause of cancer death across the world, and nanomedicine has provided promising alternatives for the treatment of NSCLC in recent years. Photothermal therapy (PTT) and chemodynamic therapy (CDT) have represented novel therapeutic modalities for cancer treatment with excellent performance. The purpose of this research was to evaluate the effects of PPy@Fe3O4 nanoparticles (NPs) on inhibiting growth and metastasis of NSCLC by combination of PTT and CDT. In this study, we synthesized PPy@Fe3O4 NPs through a very facile electrostatic absorption method. And we detected reactive oxygen species production, cell apoptosis, migration and protein expression in different groups of A549 cells and established xenograft models to evaluate the effects of PPy@Fe3O4 NPs for inhibiting the growth of NSCLC. The results showed that the PPy@Fe3O4 NPs had negligible cytotoxicity and could efficiently inhibit the cell growth and metastasis of NSCLC in vitro. In addition, the PPy@Fe3O4 NPs decreased tumor volume and growth in vivo and endowed their excellent MRI capability of observing the location and size of tumor. To sum up, our study displayed that the PPy@Fe3O4 NPs had significant synergistic effects of PTT and CDT, and had good biocompatibility and safety in vivo and in vitro. The PPy@Fe3O4 NPs may be an effective drug platform for the treatment of NSCLC.